2021
DOI: 10.3390/su131911100
|View full text |Cite
|
Sign up to set email alerts
|

Crowdfunding for Independent Print Media: E-Commerce, Marketing, and Business Development

Abstract: Crowdfunding, as an alternative method to fundraising, triggers increased awareness in society, while it is also an effective marketing tool for campaign runners. The production and release of independent print media poses significant hurdles in terms of financing. Including the community in raising funds through crowdfunding seems like a good possible alternative. This paper examines which types of crowdfunding the independent print media use, and why, and also focuses on the possible types of crowdfunding th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 158 publications
0
4
0
Order By: Relevance
“…The third cluster (blue) of the network is made of 47 keywords on the research stream of crowdfunding and P2P lending. The influential keywords which have maximum occurrences are community, fund raising, donation, nonprofit, and sustainability (Giudici et al 2018;Jo and Yang 2021;Konhäusner et al 2021;Wehnert et al 2019;Zheng et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The third cluster (blue) of the network is made of 47 keywords on the research stream of crowdfunding and P2P lending. The influential keywords which have maximum occurrences are community, fund raising, donation, nonprofit, and sustainability (Giudici et al 2018;Jo and Yang 2021;Konhäusner et al 2021;Wehnert et al 2019;Zheng et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Sayedi and Baghaie (2017) even suggested that CF is now being increasingly used as a marketing tool, rather than a source of funding. Only limited research has been conducted on marketing practices, specifically crowdfunding, and their effect on the efficiency of the campaign (Konhäusner et al 2021b). The present study will explain the effectiveness of crowdfunding as a communication channel for politicians and parties to communicate their political agenda and, at the same time, seek financial donations from the public.…”
Section: Literature Review and Hypotheses Buildingmentioning
confidence: 99%
“…Bholat et al (2018) measured citizens' comprehension levels of BoE publications and examined central bank communication and its effectiveness by tying it to its impact on financial markets and to the ways in which it is correlated to the inflation expectations of firms and households. Other studies show that the communication policy of the ECB reports impacts strongly financial markets and increases the interest rate of decisions' predictability (Fratzscher, 2007;Blinder et al, 2008;Konhäusner et al, 2021), thus insuring a high trust level in the content. The communication strategies of on New Trends in Sustainable Business and Consumption the Reserve Bank of Australia (Huang, 2021), of the BoE (Haldane, 2020) have also been analysed and guidance has been provided to increase citizens' engagement, understanding and expectations.…”
Section: Literature Reviewmentioning
confidence: 99%